Dexmedetomidine alleviates lipopolysaccharide‐induced acute kidney injury by inhibiting the NLRP3 inflammasome activation via regulating the TLR4/NOX4/NF‐κB pathway. Issue 10 (26th June 2019) - Yao, Yujie; Hu, Xueyuan; Feng, Xiujing; Zhao, Yuan; Song, Manyu; Wang, Chaoran; Fan, Honggang
Abstract: Dexmedetomidine (DEX) prevents kidney damage caused by sepsis, but the mechanism of this effect remains unclear. In this study, the protective molecular mechanism of DEX in lipopolysaccharide (LPS)‐induced acute kidney injury was investigated and its potential pharmacological targets from the perspective of inhibiting oxidative stress damage and the nucleotide‐binding domain‐like receptor protein 3 (NLRP3) inflammasome activation. Intraperitoneal injection of DEX (30 μg/kg) significantly improved LPS (10 mg/kg) induced renal pathological damage and renal dysfunction. DEX also ameliorated oxidative stress damage by reducing the contents of reactive oxygen species, malondialdehyde and hydrogen peroxide, and increasing the level of glutathione, as well as the activity of superoxide dismutase and catalase. In addition, DEX prevented nuclear factor‐kappa B (NF‐κB) activation and I‐kappa B (IκB) phosphorylation, as well as the expressions of NLRP3 inflammasome‐associated protein and downstream IL‐18 and IL‐1β. The messengerRNA (mRNA) and protein expressions of toll‐like receptor 4 (TLR4), NADPH oxidase‐4 (NOX4), NF‐κB, and NLRP3 were also significantly reduced by DEX. Their expressions were further evaluated by immunohistochemistry, yielding results were consistent with the results of mRNA and protein detection. Interestingly, the protective effects of DEX were reversed by atipamezole‐an alpha 2 adrenal receptor (α2 AR) inhibitor, whereas idazoxan‐an imidazoline receptor (IR) inhibitor failed to reverse this change. In conclusion, DEX attenuated LPS‐induced AKI by inhibiting oxidative stress damage and NLRP3 inflammasome activation via regulating the TLR4/NOX4/NF‐κB pathway, mainly acting on the α2 AR rather than IR. Abstract : 1. DEX alleviates LPS triggered renal oxidative stress. 2. DEX ameliorates LPS‐induced renal inflammatory response. 3. DEX inhibits NLRP3 inﬂammasome activation via TLR4/NOX4/NF‐κB pathway in LPS induced kidney injury. 4. DEX attenuates LPS‐induced acute kidney injury by acting on α2 AR, but not IR.